OC-062 A Multi-centre Pragmatic Study Of An Educational Intervention To Improve Adenoma Detection At Colonoscopy. (9th June 2014) - Rajasekhar, PT; Rees, CJ; Rutter, MD; Saunders, BP; Bramble, MG; Hungin, P; Wilson, DW; East, JE
Abstract : Introduction: High quality colonoscopy prevents colorectal cancers. Low adenoma detection rates (ADR) are linked to subsequent high interval cancer rates. Variability in ADR exists between practitioners. Withdrawal time of >6 min, Buscopan use, position change and rectal retroflexion have some evidence to improve lesion detection. Implementation of evidence based 'bundles' of care has shown to be effective in improving outcomes in other clincal settings [1] . Methods: We aimed to evaluate the feasibility of implementing a 'bundle' comprising the above measures into routine practice and effect on ADR. Twelve English endoscopy units participated. All nominated a lead endoscopist and nurse. A model combining central training, locally led implementation, feedback and ongoing study team support was used. Colonoscopist's ADRs were measured for 3 months prior to implementation and for a 9 month period following. Colonoscopists performing ≥25 procedures during the period before were ranked according to ADR and quartiles constructed. Change in Buscopan use was used as a surrogate marker for intervention uptake. A corrected Chi Squared test was used to check for significant change. Results: One hundred and eighteen and 68 colonoscopists were included in the global and quartile analyses. The study included 17508 colonoscopies, 4351 and 13157 in the pre and post intervention periods respectively. There was a significant global increase in buscopan use (15.8 vs. 54.4%, p < 0.001), also seen in each quartile, and ADR (16.0 vs. 18.1%, p = 0.002), Table 1 . Conclusion: Our evidence based educational intervention resulted in a significant change in behaviour, evidenced by increased Buscopan use. A significant increase in ADR occurred globally and in the two lower quartiles. A fall was seen in the upper quartile, but the ADR in this group remained above that in the other groups and the global mean of 18.1%. This study demonstrates that simple evidence based educational interventions with support can significantly change practice and ADR, particularly amongst the poorest performers. Reference: 1 Pronovost P et al . An intervention to decrease catheter-related bloodstream infections in the ICU. N Engl J Med 2006:355:2725–32 Disclosure of Interest: None Declared.